Application of outpatient cardiac testing among emergency department patients with syncope. Issue 8 (24th April 2018) - Cook, Olivia G; Mukarram, Muhammad A; Kim, Soo-Min; Arcot, Kirtana; Nemnom, Marie-Joe; Taljaard, Monica; Sivilotti, Marco L A; Rowe, Brian H; Thiruganasambandamoorthy, Venkatesh
Abstract : Objectives: 2.6% of ED syncope patients will suffer cardiac serious adverse events (SAEs) within 30 days of disposition, and outpatient cardiac testing can improve patient safety. The objective is to determine whether outpatient cardiac testing for ED syncope patients is being appropriately ordered after discharge. To this end, we describe the proportion of high-risk and non-high (low and medium)-risk ED syncope patients as per the Canadian Syncope Risk Score (CSRS) who have a SAE after ED discharge, and the proportion referred for outpatient cardiac testing. Methods: Our multicentre prospective cohort study enrolled adult syncope patients between 2010 and 2014 in five academic EDs. We collected patient characteristics, disposition, CSRS predictors, outpatient referrals and testing results (Holter, echocardiography), and 30-day adjudicated SAE (death due to unknown/cardiac cause, myocardial infarction, arrhythmia and structural heart disease). We used descriptive statistics (mean, SD) to report our results. Results: Of 3584 enrolled patients (mean age 50.9 years, 57.7% women), 800 patients (22.3%) received an outpatient referral. Of these 800 patients, 40.3% of the non-high-risk patients (305/756) and 54.5% of the high-risk patients (24/44) received outpatient cardiac testing. Of all patients who received cardiac testing, five (1.5%; 95% CI 0.6% to 3.5%) suffered outpatient SAE (60.0% arrhythmias). Of all patients who did not receive cardiac testing, four patients (0.9%; 95% CI 0.3% to 2.2%) suffered SAE (all arrhythmias). Of the 20 (45.5%) high-risk patients who did not receive testing, two patients (10.0%; 95% CI 2.8% to 30.1%) suffered arrhythmias outside the hospital, while among the 451 (59.7%) non-high-risk patients, only two (0.4%; 95% CI 0.1% to 1.6%) suffered outpatient arrhythmias. Conclusion: Outpatient cardiac testing is largely underused, especially among high-risk ED syncope patients. Better guidelines for outpatient cardiac testing are needed, as the practice is highly variable and mismatched with patient risk.